Comparison of Topical Adapalene and Electrocautery in Treatment of Plane Warts - Maryam Tahir, Tahir Hassan, Muhammad Khurram Shahzad, Nazia Hanif, Naima Aliya, Madiha Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Warts are lesions that grow on the human skin due to infection named human papilloma-virus (HPV) type 1, 2, and 4. More than 100 types of HPV virus have been identified now. Aim: To compare the efficacy of adapalene and electrocautery therapies in managing plane warts. Study design: Randomized Control Trial. Methodology: A total of 52 patients via non probability consecutive sampling technique with plane warts were enrolled and randomly divided into 2 equal groups. The patients of Group A were treated with 0.5% Adapalene gel (applied twice daily over the lesions for maximum 3 months or until resolution of warts) and patients in group B were treated with electro-cautery procedure fortnightly for maximum 3 months or until resolution of warts). Patients were assessed after every 2 weeks for initial 3 months and then these patients were followed monthly for another 3 months and final outcome was seen at 6 months. Data was evaluated by using SPSS version 23. Student-t test was applied with p-value than 0.05 taken as significant. Results: The mean duration of wart resolution was observed as 45.92±19.22 days in the adapalene group, while the electro-cautery procedure took 45 ± 17.81 days for wart clearance. There were no statistically significant differences in the complications between the two groups (p=0.60). Practical Implication: Although successful outcomes have been achieved in many studies by using Adapalene and electrocautery separately for treating warts but none of the published research compares these two treatment modalities (Adapalene vs electrocautery) for treatment of plane warts as per our knowledge. Therefore to fill this gap, this study was designed to compare the efficacy of adapalene and electrocautery therapies. Conclusion: It was concluded that Both Adapalene and electrocautery are effective in treatment of plane warts and there are no statistically significant differences in the complications/side effects of these two treatment modalities. Keywords: Adapalene Gel 0.1%, Electrocautery, Plane Warts, Clinical Outcomes and Effectiveness.